2020
DOI: 10.1002/jemt.23572
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic and histological studies of the buccal cavity of a phytoplanktivorous small freshwater fish, Amblypharyngodon mola

Abstract: The electron microscopic and histological studies of the buccal-cavity of herbivorous fish Mola (Amblypharyngodon mola) were performed. The studies revealed that the architectures of the buccal cavity of A. mola support the herbivory nature of the fish. Both the upper and lower jaws of the fish are rich in mucus glands, unculi, and microridges. The presence of papillae like taste buds in the lower jaw of A. mola indicates the mechanosensory role of the lower jaw during gustation. These features directly suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The observed upper velum act as a valve regulating the water passage into the buccal cavity as reported in the previously published data (Abumandour, 2019; Abumandour & El‐Bakary, 2017; Abumandour & Gewaily, 2016; Alsafy et al, 2021; Coxon & Davison, 2011; El Bakary, 2012; El‐Gendy et al, 2016; Fishelson et al, 2004; Fishelson et al, 2012; Fishelson & Delarea, 2004; Nandi & Saikia, 2021; Yashpal et al, 2006; Yashpal et al, 2009). The current description of the upper and lower velum as the semilunar thin membrane was similar to that reported in different fish‐species of the different feeding habits (Alsafy et al, 2021; El Bakary, 2012; El Bakary, 2014; El‐Gendy et al, 2016; Fishelson et al, 2004; Fishelson et al, 2012; Fishelson & Delarea, 2004; Yashpal et al, 2006; Yashpal et al, 2009).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The observed upper velum act as a valve regulating the water passage into the buccal cavity as reported in the previously published data (Abumandour, 2019; Abumandour & El‐Bakary, 2017; Abumandour & Gewaily, 2016; Alsafy et al, 2021; Coxon & Davison, 2011; El Bakary, 2012; El‐Gendy et al, 2016; Fishelson et al, 2004; Fishelson et al, 2012; Fishelson & Delarea, 2004; Nandi & Saikia, 2021; Yashpal et al, 2006; Yashpal et al, 2009). The current description of the upper and lower velum as the semilunar thin membrane was similar to that reported in different fish‐species of the different feeding habits (Alsafy et al, 2021; El Bakary, 2012; El Bakary, 2014; El‐Gendy et al, 2016; Fishelson et al, 2004; Fishelson et al, 2012; Fishelson & Delarea, 2004; Yashpal et al, 2006; Yashpal et al, 2009).…”
Section: Discussionsupporting
confidence: 57%
“…The buccal cavity of fish plays an important role in prey capture and food transportation and help in the fish adaptation to the surrounding environmental conditions (Alexander, 1967; Alsafy et al, 2021; Cataldi et al, 1987; El‐Gendy, Alsafy, & Tanekhy, 2016; Elshoud‐Oldenhave & Osse, 1976). Previously, the oropharyngeal cavity was described by the SEM investigations in the different feeding habits fish‐species; carnivorous species (Alsafy et al, 2021; Bishop & Odense, 1966; Cataldi et al, 1987); plankton feeder species, (Chakrabarti & Sinha, 1987; Nandi & Saikia, 2021; Sinha & Chakrabarti, 1985), herbivorous species (Atkinson & Collin, 2012; El Bakary, 2011; El Bakary, 2012; Yashpal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…current observation of the white grouper E. aeneus in the two age stages (juvenile and adult) observed that the thin semilunar membranous lower velum was located at the inner boundary of the jaw and had two surfaces, two borders and two parts (two laterally situated narrow parts and a single median wide part). The presence of the oral cavity velum was observed previously byAbumandour et al (2021),Alsafy et al (2018), El Bakary (2012), Fishelson, Baldwin, and Hastings (2012,Nandi and Saikia (2021), Yashpal, Kumari, Mittal, and Mittal (2006), and Yashpal, Kumari, Mittal, and Mittal (2009. However, in the Carp Cirrhinus mrigala, the lower velum not observed(Yashpal, Kumari, Mittal, & Mittal, 2009), while Coxon and Davison (2011)) described the presence of cartilaginous velum in the New Zealand hagfish Eptatretus cirrhatus.…”
mentioning
confidence: 71%
“…However, the edentulous jaws were recorded in the herbivorous fish due to the food particle grasps and holding not need the presence of the teeth as reported in several fishes such as in; the flatfish common solea (El Bakary, 2014), Cirrhinus mrigala (Khanna, 1962; Sastry, 1973), the gilthead seabream (Abbate et al, 2012), Carp C. mrigala (Khanna, 1962) and Labeo horie , Hilsa and Mugil (Sastry, 1973). However, the complete absence of the papillary‐like teeth was observed in numerous teleost fishes as recorded by Islam (1951) and Nandi and Saikia (2020), while Khanna (1962), described the presence of this papilliform teeth on the pre‐maxillae but not on dentaries. Functionally, the presence of the teeth bands on the upper and lower jaws of the white grouper ( E. aeneus ) fish had special adaptation to performing the capturing predatory behavior (Mihalitsis & Bellwood, 2019; Reimchen, 1991).…”
Section: Discussionmentioning
confidence: 94%